Pinart and Balonchard, Type Founders in Rio de Janeiro during the 19th century - Lima, Edna Lucia Cunha (InfoDesign, 2009)
This paper on type foundries in Rio de Janeiro during the 19th century, Pierre Joseph Pinart and Isaac Balonchard,. This research was undertaken by consulting the Brazilian National Library (newspapers and almanacks) and the Brazilian National archives (registers of entries of foreigners).